A Facile and Inexpensive Way to Synthesize N‐trifluoromethyl Compounds. Issue 23 (17th June 2022) - Schaub, Stefan; Becker, Jonathan; Schindler, Siegfried
Abstract: A facile way to introduce CF3 groups on a large variety of secondary amines has been developed, avoiding expensive and hazardous reagents. The advantage of the method could be demonstrated by obtaining crystalline tert ‐butyl 4‐(trifluoromethyl)piperazine‐1‐carboxylate, a compound that previously only had been obtained as an oil. A major problem is the extreme sensitivity of these compounds towards moisture. Abstract : Improved new method for the synthesis of trifluoromethyl amines (R, R1 = different carbon chains, any secondary amine). The precursor electrophile is commercially available, and all reagents applied are inexpensive. Products can be obtained in pure form, however, they are extremely sensitive to moisture.